2004
DOI: 10.1161/01.cir.0000124723.16433.31
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Left Ventricular Diastolic Function by Tissue Doppler Imaging and Clinical Status in Children With Hypertrophic Cardiomyopathy

Abstract: Background-Conventional

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
3
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(149 citation statements)
references
References 39 publications
2
139
3
5
Order By: Relevance
“…Left atrial size was investigated as a risk factor for SCD in three studies 20,24,25 and CVD in two studies 20,24 …”
Section: Left Atrial (La) Sizementioning
confidence: 99%
“…Left atrial size was investigated as a risk factor for SCD in three studies 20,24,25 and CVD in two studies 20,24 …”
Section: Left Atrial (La) Sizementioning
confidence: 99%
“…Estes dois animais apresentavam valores de E/Em superiores a 15 na maioria dos cortes ecocardiográficos, avaliados pelo Doppler tecidual pulsado e Doppler tecidual colorido, descritos anteriormente. Segundo McMahon et al (2004), relação E/Em elevada é indicativa de maior risco de morte súbita, parada cardíaca e taquicardia ventricular em crianças com CMH. De acordo com Graziano & Acquatella (2007), a relação E/Em associa-se, também, à capacidade funcional e ao consumo de oxigênio em adultos com CMH.…”
Section: Discussão E Conclusõesunclassified
“…In children with dilated cardiomyopathy, only early diastolic velocity at the tricuspid annulus Ea < 8.5 cm/sec and LVEF < 30% represented negative prognostic predictors in multivariate analysis [31]. In children with hypertrophic cardiomyopathy, the septal E/Ea ratio proved to be a significant unfavorable prognostic predictor [32]. Other studies have shown the utility of TDI parameters in the early identification of heart transplantation rejection in pediatric patients [33,34].…”
Section: Discussionmentioning
confidence: 96%